DESIGNING EPT TRAINING SYLLABUSES FOR NON-ENGLISH DEPARTMENT STUDENTS OF UNIPDU JOMBANG (A STUDENTS’ NEEDS ANALYSIS) - Ahmad Fanani (Educate, 2012)
Achmad Fanani Universitas Pesantren Tinggi Darul Ulum Jombang akufanani@gmail.com  Abstract The EPT test is an internationally accepted standard of English that measures the academic English proficiency of a non-native speaker of English. This research is aimed at designing EPT training syllabuses that meet the needs of non-English department students of UNIPDU Jombang with low level of English proficiency. In general, the contents of the syllabuses based on the students’ needs analysis are as follows: 1. Listening comprehension: PART A:  meaning questions, suggestion, prediction, implication, inferences, PART B: topics of conversations, details of conversations, PART C: topics of talks/lectures, details of talks/lectures; 2. Structure and Written Expression: a. Incomplete sentences: conjunctions, comparisons, subject missing, adjective clauses, b. Underlined words: count/non-count nouns, banana rule, adjectives, prepositions, noun-pronoun agreement, singular/plural nouns; 3. Reading Comprehension and Vocabulary: References, passage organization, exception, inferences, topics, main ideas. Keywords: EPT, students’ needs, syllabuses   Abstrak EPT test adalah tes Bahasa Inggris berstandard internasional yang mengukur kemampuan bahasa Inggris akademik para petutur bahasa Inggris non-native. Penelitian ini dimaksudkan untuk mendesain silabus untuk pelatihan EPT yang memenuhi kebutuhan mahasiswa dari jurusan non bahasa Inggris UNIPDU Jombang yang berkemampuan bahasa Inggris kurang. Secara umum isi dari silabus berdasar analisis kebutuhan siswa adalah sebagai berikut: 1. Listening comprehension: PART A:  meaning questions, suggestion, prediction, implication, inferences, PART B: topics of conversations, details of conversations, PART C: topics of talks/lectures, details of talks/lectures; 2. Structure and Written Expression: a. Incomplete sentences: conjunctions, comparisons, subject missing, adjective clauses, b. Underlined words: count/non-count nouns, banana rule, adjectives, prepositions, noun-pronoun agreement, singular/plural nouns; 3. Reading Comprehension and Vocabulary: References, passage organization, exception, inferences, topics, main ideas. Kata kunci: EPT, kebutuhan siswa, silabus